The Relationship between Parental Involvement and the Students’ Achievement at the Eighth Grade Students of MTs Negeri 1 Makassar - Hamid, Sitti Maryam (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2018)
The objective of this research were to analyze: (1) parental involvement in the students’ achievement at the Eighth Grade Students of MTsNegeri 1 Makassar. (2) the relationship between parental involvement and students’ achievement at the eighth grade students of MTsNegeri 1 Makassar.The researcher used descriptive correlation research. There were two variables in this research, namely parental involvement (variable X) and the students’ English achievement (variable Y). The technique of collecting data used questionnaire and documentation. The questionnaire consisted of 24 items. The sample of this research was 42 students.The result of the research showed that forms of parental involvement are found at the eighth grade of MTsNegeri 1 Makassar, the mean score of parenting was 3.20, communicating was 2.76, volunteering was 2.43, learning at home was 2.49, decision making was 2.78, collaborating with community was 2.53, and the total of the mean score was 16.19. It means that parental involvement of the eighth grade students of MTsNegeri 1 Makassar is low level. Based on the result of the research, it showed that there was a relationship between parental involvement and students’ English achievement at the eighth grade students of MTsNegeri 1 Makassar in Academic Year of 2018/2019 because r = 0,125.